PENGARUH KUALITAS PELAYANAN KESEHATAN TERHADAP KEPUASAN PENGGUNA BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) DI RUMAH SAKIT BHAYANGKARA SURABAYA TAHUN 2016 - Sany, Adillia Anora Ivanda (Universitas 17 Agustus 1945 Surabaya, 2018)
Influence of health service quality to user satisfaction of social insurance provider institution (BPJS) at Bhayangkara Hospital Surabaya 2016. The hospital is as a public health care provide services that are effective, efficient and required to each patient. The patient satisfaction is as a benchmark level of quality health services. This study aims to determine and analyze the influence of the quality of hospital services Bhayangkara Surabaya to client satisfaction BPJS users as well as identify and analyze the application of Community Satisfaction Indicators according to the rules Menpan and Bureaucratic Reform Indonesia. The research method is descriptive used a questionnaire or questionnaires by interviews and observation. Mechanical analysis used quantitative descriptive analysis. There are 20 respondents surveyed in this study by answering questions based on a questionnaire given to assess public opinion about the quality of sevice and its effects on people's satisfaction. Independent variables namely the quality of service and the dependent variable is community satisfaction. The results based on the results of the processing of qualitative data through interviews and observations in general satisfaction of the public regarding the quality of hospital services Bhayangkara especially give well satfisfaction to members of BPJS. This indicates that the RS Bhayangkara constantly working on providing the best service for society to improve and try to give satisfaction to the public.Â Â Keywords: Quality of Service, Society Satisfaction, RS Bhayangkara